1994
DOI: 10.1002/j.1875-9114.1994.tb02792.x
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Sodium Bicarbonate Regimen During Cardiac Arrest and Cardiopulmonary Resuscitation in a Canine Model

Abstract: We evaluated the effect of frequent, early bolus administration of low-dose sodium bicarbonate (NaHCO3) on blood gas values during ventricular fibrillation and cardiopulmonary resuscitation (CPR) compared with normal saline and standard bolus doses of NaHCO3. This was a randomized laboratory investigation involving 13 mongrel dogs and 18 experiments (5 dogs were used in a crossover manner). Each dog underwent 3 minutes of ventricular fibrillation, followed by 15 minutes of CPR. Animals were randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In the first study, different dosages and modes of sodium bicarbonate therapy were investigated, and it was confirmed that alkalosis developed in response to bicarbonate therapy . In the second study evaluating an early bolus of low‐dose sodium bicarbonate during VF, the investigators found that it was still associated with the development of an alkalosis . Finally, the efficacy of epinephrine as a vasopressor when used in combination with bicarbonate therapy was evaluated in a VF model in dogs .…”
Section: Other Drug Therapymentioning
confidence: 97%
“…In the first study, different dosages and modes of sodium bicarbonate therapy were investigated, and it was confirmed that alkalosis developed in response to bicarbonate therapy . In the second study evaluating an early bolus of low‐dose sodium bicarbonate during VF, the investigators found that it was still associated with the development of an alkalosis . Finally, the efficacy of epinephrine as a vasopressor when used in combination with bicarbonate therapy was evaluated in a VF model in dogs .…”
Section: Other Drug Therapymentioning
confidence: 97%
“…Several experimental studies in dogs have documented improved survival with bicarbonate therapy with prolonged (>10 min) duration of CPA . However, other experimental studies in dogs have demonstrated worse outcomes and metabolic derangements with bicarbonate therapy, especially when given early in CPR . Given the evidence available, bicarbonate therapy after prolonged CPA of greater than 10–15 minutes with administration of 1 mEq/kg of sodium bicarbonate may be considered (IIb‐B).…”
Section: Alsmentioning
confidence: 99%